Roughness of a subglacial conduit under Hansbreen, Svalbard - Mankoff, Kenneth D.; Gulley, Jason D.; Tulaczyk, Slawek M.; Covington, Matthew D.; Liu, Xiaofeng; Chen, Yunxiang; Benn, Douglas I.; GŁowacki, Piotr S. (Journal of Glaciology, 2017)
K.M., J.G., X.L. and Y.C. were supported by the National Science Foundation (NSF) under Grant No. #1503928. Thefieldwork team (K.M., J.G., M.C.) were supported by the Norwegian Arctic Research Council and Svalbard Science Forum, RiS #6106. K.M. was also supported by the National Aeronautics and Space Administration (NASA)Headquarters under the NASA Earth and Space Science Fellowship Program – Grant NNX10AN83H, the University of California, Santa Cruz, and the Woods Hole Oceanographic Institution Ocean and Climate Change Institute post-graduate fellowship. Portions of this work were conducted while J.G. was supported by the NSF EAR Postdoctoral Fellowship (#0946767). S.T. was funded by NASA grant NNX11AH61G. Hydraulic roughness exerts an important but poorly understood control on water pressure in subglacial conduits. Where relative roughness values are <5%, hydraulic roughness can be related to relative roughness using empirically-derived equations such as the Colebrook-White equation. General relationships between hydraulic roughness and relative roughness do not exist for relative roughness >5%. Here we report the first quantitative assessment of roughness heights and hydraulic diameters in a subglacial conduit. We measured roughness heights in a 125 m long section of a subglacial conduit using structure-from-motion to produce a digital surface model, and hand-measurements of the b-axis of rocks. We found roughness heights from 0.07 to 0.22 m and cross-sectional areas of 1-2 m2, resulting in relative roughness of 3-12% and >5% for most locations. A simple geometric model of varying conduit diameter shows that when the conduit is small relative roughness is >30% and has large variability. Our results suggest that parameterizations of conduit hydraulic roughness in subglacial hydrological models will remain challenging until hydraulic diameters exceed roughness heights by a factor of 20, or the conduit radius is >1 m for the roughness elements observed here. Peer reviewed